Fusarium mirum sp. nov, intertwining Fusarium madaense and Fusarium andiyazi, pathogens of tropical grasses. Issue 3 (March 2022) - Costa, Marileide M.; Saleh, Amgad A.; Melo, Maruzanete P.; Guimarães, Elaine Aparecida; Esele, J. Peter; Zeller, Kurt A.; Summerell, Brett A.; Pfenning, Ludwig H.; Leslie, John F.
Abstract: Many species in the Fusarium fujikuroi Species Complex (FFSC) have an affinity for grass species, with whom they live in an endophytic association or cause disease. We recovered isolates of Fusarium from agriculturally important grasses in Africa and Brazil, and characterized them with morphological markers, mating type, and Amplified Fragment Length Polymorphisms (AFLPs). We also conducted multi-locus phylogenetic analyses based on partial DNA sequences of translation elongation factor-1α ( TEF1 ), β-tubulin ( TUB ), and the second largest subunit of RNA polymerase ( RPB2 ) gene regions. Sexual cross fertility was used to test the biological species concept and the sexual stage of F. madaense is described. A novel species within the FFSC, Fusarium mirum, that is different from the other known species in the complex, was formally described. Fusarium mirum, F. madaense, and Fusarium andiyazi are a tightly intertwined species trio that are morphologically identical, but phylogenetically distinguishable, and amongst whom interspecific genetic exchange may still occur. These three species are so close that they cannot be reliably distinguished if only sequences of the TEF1 gene are used. In pathogenicity tests, all tested isolates of F. madaense from sugarcane, sorghum, maize, millet and Brachiaria could induce stalk rot in sorghum, maize and millet, and pokkah boeng in sugarcane. This study increases our understanding of the diversity of species within the FFSC that cause disease in tropical grasses or act as endophytes, and their geographic distributions. The genetically close relationship between F. mirum, F. madaense, and F. andiyazi provides an opportunity to study and identify factors underlying their limited inter-specific cross-fertility and sympatric speciation. Highlights: Described a new species, F. mirum, closely related to F. madaense and F. andiyazi Demonstrated pathogenicity of F. madaense and F. mirum on multiple known hosts TEF-1 is very highly polymorphic amongst F. mirum, F. madaense and F. andiyazi Some strains identified as F. andiyazi based on TEF-1 probably are F. madaense